2005
DOI: 10.1088/0954-3899/31/9/003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the strength of hyperon–hyperon interactions on neutron star properties

Abstract: Abstract. An equation of state of neutron star matter with strange baryons has been obtained. The effects of the strength of hyperon-hyperon interactions on the equations of state constructed for the chosen parameter sets have been analyzed. Numerous neutron star models show that the appearance of hyperons is connected with the increasing density in neutron star interiors. The performed calculations have indicated that the change of the hyperon-hyperon coupling constants affects the chemical composition of a n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Therefore, there has to be a mechanism that suppresses (or removes) the amount of hyperons at densities relevant for compact star physics. One possibility is the vector repulsion of hyperons generated by the exchange of the φ meson [3][4][5]. This finding reinforces the point that when including hyperons as parts of the baryon octet, one should also take into account the corresponding SU(3) multiplets in the meson sector.…”
Section: Modeling Compact Starssupporting
confidence: 64%
“…Therefore, there has to be a mechanism that suppresses (or removes) the amount of hyperons at densities relevant for compact star physics. One possibility is the vector repulsion of hyperons generated by the exchange of the φ meson [3][4][5]. This finding reinforces the point that when including hyperons as parts of the baryon octet, one should also take into account the corresponding SU(3) multiplets in the meson sector.…”
Section: Modeling Compact Starssupporting
confidence: 64%
“…The Nagara event provides unambiguous identification of 6 ΛΛ He production with a precise ΛΛ binding energy value B ΛΛ = 7.25 ± 0.19 +0.18 −0.11 MeV, which suggests that the effective ΛΛ interaction should be considerably weaker (△B ΛΛ ≃ 1 MeV) than that deduced from the earlier measurement (△B ΛΛ ≃ 4-5 MeV). The weak hyperonhyperon (Y Y ) interaction suggested by the Nagara event has been used to reinvestigate the properties of multistrange systems, and it has been found that the change of Y Y interactions affects the properties of strange hadronic matter dramatically [29,30,31]. We would like to examine how the Y Y interaction affects the properties of hyperonic matter in the presence of strong magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…MeV, while the strong Y Y interaction deduced from the earlier measurement suggests U (Λ) Λ ≃ −20 MeV[27,29,30,31]. In…”
mentioning
confidence: 99%
“…MeV [25] permits the existence of additional parameter set [26] which reproduces this weaker ΛΛ interaction. In the text this parameter set is marked as weak, whereas strong denotes the stronger ΛΛ interaction for U (Λ) Λ ≃ 20 MeV [12].…”
Section: The Equation Of State and The Equilibrium Conditionsmentioning
confidence: 99%